Epigenetic laterality differences in breast cancer - Masuelli, Sofía (2019)
Breast Cancer is a heterogeneous disease. By previous studies we determined that mammary tumors of left-right sides (L-R) differ in their behavior as inferred from their methylation profiles. Normal breast L-R tissues have not identical environments; they differ in size, irrigation and fat composition. It is also known that epigenetics functions as a bridge between environment and gene expression. Our hypothesis sustains that L-R tumors differ in epigenetically regulated pathways, provoked by the diverse L-R microenvironment. To study this, we performed in-silico and invivo analyses. From database c-BioPortal Provisional Breast Cancer, 708 tumors with information for 16.000 genes were included and L-R methylation medias were compared for each gene. The top 169 genes with significant L-R difference above 3% were selected (T test, p<0.0001) and filtered by cancer related search terms in Metascape. Fifty three genes were associated with the terms “inflammation”, “proliferation negative regulation”, “immune response”, “DNA damage response”, “P53 pathway”, “angiogenesis”, “migration”, “cell death regulation”, “survival” and “apoptosis”. Then, the methylation profiles were converted into the 7 cancer terms. Interestingly, the cancer term profiles clustered into 2 groups associated with L-R laterality (Hierarchical cluster analysis, bootstrap 90-100 %), suggesting the existence of different L-R methylation profiles associated with functional terms. In the invivo studies, the methylome of 6 L-R xenografts generated by inoculation of MDA-MB231 cells in NSG mice were analyzed by RRBS. Preliminary analyses reveal 197 gene promoters, with significant L-R difference (FDR corrected p<0.01). Further functional and expression studies will allow to evaluate the impact of these methylation differences on the tumor behavior. So far, our studies support an interesting epigenetic related laterality hypothesis for breast cancer, which could serve as proof of principle for other bilateral tumors.